Social and International Identity of Students’ Personality in the Globalized World: Vietnamese Students’ Experience - O. A. Kulikova (Управление)
This paper is based on the results of studying in Moscow higher educational institutions Vietnamese students’ depth interview. Research is devoted to how students from other countries build their identification, attracting their social communications networks. This research results allow understand how foreign students face and cross cultural distinctions to define new prospects of identity that gives them a chance to perform special social roles and increase their national and heritage identity. This paper suggests that international educational programs originators consider cultural diversity, recognizing social and cultural influences as defining factors in foreign students’ learning and everyday life, to make the curriculum and use pedagogical methods which give a chance to foreign students to develop self-knowledge, openness and citizenship.